2018
DOI: 10.1186/s40104-018-0285-6
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations in the uterine luminal fluid composition are detrimental to pregnancy establishment in cattle

Abstract: BackgroundA major, unresolved issue is how the uterine microenvironment determines pregnancy success in cattle. Before implantation, conceptus development depends on the uterine secretome (i.e., histotroph). Despite its pivotal role, little is known about the dynamics of histotroph synthesis and changes in composition throughout the early diestrus and the relevance to pregnancy establishment. We hypothesize that disturbances on histotroph composition affect the establishment of pregnancy. Aim was to disturb hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Placement of a large volume of fluid (30 mL) can increase the accumulation of proteins in the uterine lumen and compromise embryo survival ( Martins et al, 2018b ). Whether a smaller volume of fluid such as that in a 0.25-mL ET straw also causes deleterious changes in the uterine fluid composition is unknown.…”
Section: Causes Of Pregnancy Loss Associated With Etmentioning
confidence: 99%
“…Placement of a large volume of fluid (30 mL) can increase the accumulation of proteins in the uterine lumen and compromise embryo survival ( Martins et al, 2018b ). Whether a smaller volume of fluid such as that in a 0.25-mL ET straw also causes deleterious changes in the uterine fluid composition is unknown.…”
Section: Causes Of Pregnancy Loss Associated With Etmentioning
confidence: 99%
“…Berkkanoglu et al (2006) reported no detrimental effect of uterine flushing immediately prior to embryo transfer in human. Martins et al (2018), however, showed that bovine uteri needed 4 days to recover from the flushing disruption to return to normal pregnancy rates.…”
Section: Sampling or Chemical Processingmentioning
confidence: 99%
“…The respective proteins have immunomodulatory and metabolic functions and regulate growth and angiogenesis [ 27 ]. Minor alterations in the secretome composition have been reported to impair early pregnancy in cattle [ 28 , 29 ]. IFNτ is also known to have immunosuppressive functions.…”
Section: Introductionmentioning
confidence: 99%